2006
DOI: 10.1002/biof.5520270115
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, oxidative stress and risk of cardiovascular disease in the elderly. Protective role of antioxidant functional foods

Abstract: Free radicals and oxidative stress are involved in the pathogenic mechanisms of cardiovascular disease (CVD), diabetes and cancer. Exercise is a useful strategy for preventing CVD but in elderly persons it can enhance oxidative stress, which is why some studies recommend antioxidant supplementation for exercising elderly subjects. This intervention study was performed on 320 elderly subjects following a Geriatric Revitalization Program (GEREPRO) to maintain physical health and reduce CVD risk. GEREPRO was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…A significant increase in the concentration of SOD, TBARS and O 2 U− coupled with a decrease in the total SH group content in the high risk group compared with the lowrisk group was evident (Table 2). CVDs are more often than not linked to conditions of oxidative stress [33]. Jung et al [34] found significantly higher levels of TBARS in CVD patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…A significant increase in the concentration of SOD, TBARS and O 2 U− coupled with a decrease in the total SH group content in the high risk group compared with the lowrisk group was evident (Table 2). CVDs are more often than not linked to conditions of oxidative stress [33]. Jung et al [34] found significantly higher levels of TBARS in CVD patients compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…Galán et al [32] examined 320 participants aged 58-86 years divided into two groups. The first group (EXEr) exercised 3 times a week under the supervision of a physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacotherapy by dietary factors plays a key role in the development of various human diseases, including diabetes and immune system [14,21,32,37]. Medicinal plants continue to provide valuable therapeutic agents, in both modern medicine and traditional systems [22].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that insulin has become one of the most important therapeutic agents known to medicine, researchers have been making efforts to find insulin substitutes from synthetic or plant sources for the treatment of diabetes. Many herbs have remained as an alternative to conventional therapy especially in poor areas where insulin is not readily available [14,32].…”
Section: Introductionmentioning
confidence: 99%